PENINGKATAN HASIL BELAJAR SISWA TENTANG KONSEP PECAHAN MELALUI PENERAPAN PENDEKATAN REALISTIC MATHEMATIC EDUCATION (RME) DALAM PEMBELAJARAN MATEMATIKA - Fadhli Dzil Ikrom; Sehabudin Sehabudin (LPPM Universitas Bina Bangsa, 2023)
Fractions are one of the most fundamental concepts in learning mathematics, so that fractions become a very important material in learning mathematics at the elementary school level. However, some students at Seroja Elementary School thought that fraction material was so difficult because they did not understand the concept of fractions well. This can be seen from the results of student learning which shows that the average grade obtained is still low. The method used is classroom action research conducted in three cycles. The research model applied is the model developed by Kemmis and MC Taggart which is generally carried out in four stages, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. The research subjects in an effort to improve student learning outcomes through the application of the RME approach in learning were fourth grade students of Seroja State Elementary School, Serang City, Banten. The results of this study in classroom action research prove that the teacher's ability to apply the RME approach to learning mathematics about the concept of fractions increases and student learning outcomes increase. It can be concluded that there has been an increase in the teacher's ability to apply the RME approach to the concept of fractions in learning elementary mathematics. Furthermore, student learning outcomes regarding the concept of fractions have increased through the application of the RME approach in learning mathematics at SDN Seroja